S.T.S. dan Masalah Diagnose Syphilis - Soedarmadi, Soedarmadi (Universitas Gadjah Mada, 1974)
The Wassermann, Kahn and VDRL reactions are usually done routinely. A diagnosis based sorely on STS reaction is not recommended, although all of the three reactions are positive, moreover a diagnosis based only on one positive STS reaction is of small significant without clinical diagnosis and history of suspected syphilis. Non-specific STS is better for routine testing and for screening, as it is more sensitive while specific STS is better for solving diagnostic problems.Arti singkatan-singkatan yang dipakai :CWR = Cardiolipin Wassermann ReactionVDRL = Veneral Disease Research LaboratoryRPR = Rapid Plasma ReaginRPCF = Reiter Protein Complement FixationKRPA = Kolmer with Reiter Protein AntigenTCF = Treponema pallidum Complement Ã¢â¬Â¢ FixationT C P = Treponema pallidum Cryolysis ProteinTPA = Treponema pallidum AgglutinationTPHA = Treponema pallidurn aem-AgglutinationTPI Treponema pallidum ImmobilizationFTA Fluorescent Treponemal AntibodyABS = Absorption